Associations of TACSTD2/TROP2 and NECTIN-4/NECTIN-4 with molecular subtypes, PD-L1 expression, and FGFR3 mutational status in two advanced urothelial bladder cancer cohorts - Bahlinger, Veronika; Branz, Annalena; Strissel, Pamela; Strick, Reiner; Lange, Fabienne; Geppert, Carol-Immanuel; Klümper, Niklas; Hölzel, Michael; Wach, Sven; Taubert, Helge; Sikic, Danijel; Wullich, Bernd; et al. (Histopathology, 2024)
Aims: Treatment options for advanced urothelial carcinoma (aUC) rapidly evolved: besides immunomodulative therapeutic options and inhibitors targeting Fibroblast growth factor receptor (FGFR) alterations, two new antibody-drug conjugates (ADC), sacituzumab govitecan (SG) and enfortumab vedotin (EV), have been approved. However, little is known about the associations of specific aUC properties and the surface target expression of TROP2 and NECTIN-4. Our aim was to characterize associations of TACSTD2/TROP2 and NECTIN-4/NECTIN-4 protein and gene expression with morphomolecular and clinicopathological characteristics of aUC in two large independent cohorts. Methods and results: The TCGA BLCA (n = 405) and the CCC-EMN (n = 247) cohorts were retrospectively analysed. TROP2/TACSTD2 and NECTIN-4/NECTIN-4 are highly expressed at the protein and transcript level in aUC, and their expression status did not correlate with patient survival in both cohorts. NECTIN-4/NECTIN-4 expression was higher in luminal tumours and reduced in squamous aUCs. NECTIN-4 was negative in 10.6% of samples, and 18.4% of samples had low expression (H-score <15). The TROP2 negativity rate amounted to 6.5%. TACSTD2 and NECTIN-4 expression was reduced in neuroendocrine-like and/or protein-based double-negative tumours. TROP2- and NECTIN-4-negative tumours included one sarcomatoid and four neuroendocrine aUC. FGFR3 alterations and PD-L1 expression on tumour and immune cells did not associate with TROP2 or NECTIN-4 expression. Conclusions: TACSTD2/TROP2 and NECTIN-4/NECTIN-4 are widely expressed in aUC, independent of FGFR3 alterations or PD-L1 expression, thus representing a suitable target for ADC treatment in the majority of aUC. The expression loss was associated with aggressive morphomolecular aUC subtypes, i.e. neuroendocrine(-like) and sarcomatoid aUC.
CRIS-Team Scopus Importer:2024-01-19
Keywords: Advanced urothelial carcinoma; membranous expression; NECTIN-4/NECTIN-4; TACSTD2/TROP2; treatment options

HLA-G expression associates with immune evasion muscle-invasive urothelial cancer and drives prognostic relevance - Branz, Annalena; Matek, Christian; Lange, Fabienne; Bahlinger, Veronika; Klümper, Niklas; Hölzel, Michael; Strissel, Pamela; Strick, Reiner; Sikic, Danijel; Wach, Sven; Taubert, Helge; Wullich, Bernd; et al. (Frontiers in Immunology, 2024)
Introduction: Urothelial bladder cancer is frequent and exhibits diverse prognoses influenced by molecular subtypes, urothelial subtype histology, and immune microenvironments. HLA-G, known for immune regulation, displays significant membranous expression in tumor tissues. Methods: We studied the protein expression of Human Leucocyte Antigen G (HLA-G) in 241 Muscle-Invasive Bladder Cancer (MIBC) patients, elucidating its potential clinical and biological significance. Protein expression levels were evaluated and correlated with molecular subtypes, histological characteristics, immune microenvironment markers, and survival outcomes. Results: High HLA-G expression associates with poor overall survival (OS) and diseasespecific survival (DSS), independent of clinicopathological parameters. HLA-G expression varies among molecular subtypes and Urothelial Subtype Histology, e.g., elevated expression levels in basal/squamous MIBC and those with sarcomatoid differentiation. Notably, HLA-G is increased in MIBC with an immune evasive microenvironment (high PD-L1 tumor cell expression, NK cell depletion, granzyme B (GZMB)/CD8 ratio reduction, MHC class I (MHCI) expression reduction) that are characterized by immunosuppressive features and poor prognosis. Furthermore, HLA-G correlates with elevated levels of other immune checkpoint proteins (TIGIT, LAG3, CTLA-4), indicating its role in immune evasion. Discussion: Our findings underscore HLA-G’s role as a potential prognostic marker and interesting immunotherapeutic target in MIBC. Its impact on immune evasion mechanisms and broad expression, coupled with associations withpoor survival and distinct tumor phenotypes, positions HLA-G as a promising protein for further exploration in developing targeted immunotherapies for MIBC patients.
CRIS-Team Scopus Importer:2024-11-15
Keywords: HLA-G; immune checkpoints; immune evasion; immune microenvironment; urothelial cancer